Pemahaman dan Praktek Pola Asuh Otoriter di Sekolah House of Faith Jakarta Barat dan Implikasinya Terhadap Pendidikan Agama Kristen - Nguru, Marlina; Waruwu, Nofedin; Messakh, Jacob (Jurnal Ilmiah Wahana Pendidikan, 2026)
This paper aims to examine the understanding and practice of authoritarian parenting at the House of Faith School in West Jakarta and its implications for Christian Religious Education. Authoritarian parenting is a parenting style that emphasizes strong control, strict rules, and demands for obedience from children. This approach is often used in families and schools to foster discipline and orderly behavior in children. The research method used is descriptive with a qualitative approach. The results indicate that authoritarian parenting can foster discipline, obedience, and responsibility in children. However, excessive application has the potential to negatively impact emotional development, such as fear, lack of self-confidence, and difficulty expressing feelings and opinions. From a Christian Religious Education perspective, parenting emphasizes not only obedience but also love, patience, and role modeling. Therefore, a balance between firmness and love is necessary so that the educational process can support children's holistic development, both emotionally, socially, and spiritually.